DATA MINING DALAM PENGELOMPOKAN NILAI IQ SISWA - Alvendo Wahyu Aranski; Koko Handoko (Universitas Islam Kuantan Singingi, 2019)
Education is one aspect of life that should be owned by every human being. The most crucial times for education is during school. During school, students will start from kindergarten until finally graduating at the high school level. One aspect that is highly considered during school is the level of intelligence. Intelligence levels are often associated with IQ levels. According to research, a person's IQ level becomes a benchmark on the level of intelligence of that person. The level of intelligence can affect the lives of students in receiving lessons so well that the school should properly classify students. Grouping students based on IQ level aims that students can receive more appropriate and effective learning methods so that students can receive lessons well. At Yos Sudarso Highschool at Batam, there are a lot of students who enroll and grouping students will take a lot of time and is not efficient if done manually. Grouping students can be done quickly and precisely by utilizing data mining. One method in data mining is clustering by using K-means. The stages of this method begin with random selection K, K here is the number of clusters that you want to form. Then set K values ​​randomly, while the value becomes the center of the cluster or commonly referred to as centroid, mean or